Determinan Fiskal Dan Motivasi Manajerial Terhadap Transfer Pricing Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Sigalingging, Fritles; Nausta Pardede, Tiolina Evi (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of effective tax rate, tunneling incentive, and bonus mechanism on transfer pricing practices, with firm size as a moderating variable in automotive companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from annual financial reports and is analyzed using panel data regression. The model selection is conducted through Chow, Hausman, and Lagrange Multiplier tests, along with moderation testing to examine interaction effects. The results show that effective tax rate and bonus mechanism have a positive and significant effect on transfer pricing, while tunneling incentive has no significant effect. Furthermore, firm size is able to moderate the effect of effective tax rate on transfer pricing by strengthening the relationship, but is unable to moderate the effects of tunneling incentive and bonus mechanism. These findings indicate that tax factors and managerial incentives are the primary determinants of transfer pricing practices, while the influence of ownership structure and firm size moderation remains limited